THE DOWRY DILEMMA: EXAMINING INDIA'S DEEP-ROOTED SOCIAL EVIL - Sushil Kumar (RADJA PUBLIKA, 2022)
The dowry system in India has long been a deep-rooted social evil, posing significant challenges to gender equality and women's empowerment. This article delves into the complexities of this pervasive issue, examining its historical origins, societal impact, legal framework, and the need for change. Through a comprehensive literature review and analysis of scholarly sources, historical data, and legal documents, the article sheds light on the evolution of the dowry system in India and its enduring presence in contemporary society. It explores the social, economic, and psychological consequences faced by women and their families, highlighting the disparities and injustices that perpetuate the system. This article evaluates the effectiveness of existing legal measures and government initiatives in combatting the dowry system, aiming to identify gaps and potential areas for improvement. By examining the experiences and perspectives of those affected, it presents a compelling case for societal change, emphasizing the urgent need for gender equality, women's empowerment, and the eradication of this deep-rooted social evil. this article serves as a call to action, advocating for greater awareness, collective responsibility, and concerted efforts to address the dowry system, promoting a society where women are valued, respected, and free from the burden of dowry.